Strategi Peningkatan Kesejahteraan Nelayan dan Pembudidaya Ikan dalam Perspektif Sosial Ekonomi (Jurnal Ekonomi Laut dan Air Tawar, 2025)
Improving the welfare of fishermen and fish farmers is a strategic issue in the development of the fisheries sector in Indonesia. This study uses descriptive qualitative methods to analyze strategies that can be implemented to improve their welfare. The study covers socioeconomic factors influencing welfare, challenges faced, and potential solutions and innovations. The results indicate that strengthening market access, increasing technological capacity, business diversification, and appropriate policy support can sustainably improve the welfare of fishermen and fish farmers.